2010
DOI: 10.1111/j.1467-9922.2010.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of L1 Transfer in the Interpretation of Articles with Definite Plurals in L2 English

Abstract: This study examines second language (L2) acquisition of the interpretation of plural noun phrases. Languages with articles differ in whether they use bare plurals (English) or definite plurals (Spanish) to express generic interpretation (Chierchia, 1998;Dayal, 2004; among others). It is hypothesized that Spanish-speaking learners of English transfer the interpretation of definite plurals from their native language. Results of a truth-value judgment task provide support for this hypothesis: Spanish speakers (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
97
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 50 publications
12
97
1
2
Order By: Relevance
“…The generic interpretation is available to plural and mass (bare) NPs in the L2 for the Spanish learners and they are able to reassemble features in the L1. Our findings are similar to those of Ionin and Montrul (2010) as learners are able to move from a superset grammar to a subset grammar and are consistent with Slabakova's (2006) findings where learners can correctly move from one type of grammar to another.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The generic interpretation is available to plural and mass (bare) NPs in the L2 for the Spanish learners and they are able to reassemble features in the L1. Our findings are similar to those of Ionin and Montrul (2010) as learners are able to move from a superset grammar to a subset grammar and are consistent with Slabakova's (2006) findings where learners can correctly move from one type of grammar to another.…”
Section: Discussionsupporting
confidence: 80%
“…It should lead them to conclude that the definite article is compatible with definiteness but not with generic reference. But, positive L2 input alone is unlikely to inform the Spanish learners that definite plurals lack generic readings (see Ionin & Montrul, 2010). Spanish learners, even at advanced levels of proficiency, would be expected to incorrectly select the definite article for English bare plurals and mass generics, but would also allow/add to their interlanguage grammar the L2 form (bare NPs) and use bare plurals and definite plurals together until definite plurals are eliminated from their grammars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the English-Italian bilinguals who were living in a mostly English environment (i.e., England) were more likely to show cross-linguistic influence than those who were living in a mostly Italian environment (i.e., Italy). Evidence that variations in the input play a role in the interpretation of NPs has also been reported for Spanish heritage speakers [16,17]. Heritage speakers tend to exhibit transfer from their dominant language (e.g., English) to their heritage language (e.g., Spanish).…”
Section: Acquisition Of Bare Plurals and Definite Plurals By Bilingualsmentioning
confidence: 94%